2021
DOI: 10.1126/sciadv.abi5514
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the ATP-binding response in adenylate kinase in real time

Abstract: Time-resolved x-ray solution scattering identifies cooperative structural dynamics in the adenylate kinase enzymatic reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 88 publications
1
14
0
Order By: Relevance
“…Adenylate kinase (AdK), which catalyzes the phosphoryl transfer reaction ATP + AMP ⇌ ADP + ADP, has been widely used as a model system to study the interplay between conformational motions and enzymatic catalysis both experimentally and computationally. This enzyme is composed of three domains, i.e., the CORE domain, the LID domain (ATP binding site), and the NMP domain (AMP binding site) (Figure a and b). The catalytic cycle of AdK involves conformational transitions between a closed conformation and an open conformation.…”
Section: Introductionmentioning
confidence: 99%
“…Adenylate kinase (AdK), which catalyzes the phosphoryl transfer reaction ATP + AMP ⇌ ADP + ADP, has been widely used as a model system to study the interplay between conformational motions and enzymatic catalysis both experimentally and computationally. This enzyme is composed of three domains, i.e., the CORE domain, the LID domain (ATP binding site), and the NMP domain (AMP binding site) (Figure a and b). The catalytic cycle of AdK involves conformational transitions between a closed conformation and an open conformation.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the proposed MIP procedure involved construction of PCIs and recognition sites by adding templates in the special solvent systems of fabricated hinge-mediated MIPs on a QCM chip. Orädd et al [ 42 ] also showed the closing and opening conformational transitions that characterize conformational dynamics during AK catalysis using time-resolved X-ray solution scattering (TR-XSS). Their results demonstrated that the conformational selection in the domain closure could be considered an induced-fit mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, most enzymes do not exhibit such behav-ior, although both motor proteins and enzymes catalyze chemical reactions. In particular, enzymes exhibit a distinctive type of dynamics, i.e., conformational change, generally induced by substrate binding and product release [6,7]. Then, it follows that enzymes undergo a conformational change in each turnover cycle of the chemical reactions in the presence of substrate molecules, as shown in Fig.…”
Section: Conformational Dynamics During Chemical Reactionsmentioning
confidence: 99%
“…For the active case, however, the disturbance flow is induced even in a quiescent fluid because of the mechanical work driven by motor proteins or enzymatic molecules. Over the length scale of molecular proteins where the inertial effect is negligible, the hydrodynamic behavior is governed by the well-known Stokes equation η∇ 2 v(r) − ∇p(r) + F(r) = 0, (7) and the incompressibility condition…”
Section: A Continuum Hydrodynamic Descriptionmentioning
confidence: 99%